2004
DOI: 10.1592/phco.24.14.1295.43156
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability, Safety, Pharmacodynamics, and Pharmacokinetics of Rasagiline: A Potent, Selective, and Irreversible Monoamine Oxidase Type B Inhibitor

Abstract: Rasagiline is well tolerated at doses up to 20 mg once/day and is a potent inhibitor of platelet MAO-B in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 32 publications
1
69
0
3
Order By: Relevance
“…Rasagiline single oral doses of 1, 2, 5 and 10 mg in healthy volunteers produced approximately 35, 55, 79 and 99 % inhibition of platelet MAO-B activity at 1 h postdose [17]. The inhibition was maintained for at least 48 h post-dose and MAO-B activity returned to baseline levels after 2 weeks [17].…”
Section: Pharmacodynamic Propertiesmentioning
confidence: 92%
“…Rasagiline single oral doses of 1, 2, 5 and 10 mg in healthy volunteers produced approximately 35, 55, 79 and 99 % inhibition of platelet MAO-B activity at 1 h postdose [17]. The inhibition was maintained for at least 48 h post-dose and MAO-B activity returned to baseline levels after 2 weeks [17].…”
Section: Pharmacodynamic Propertiesmentioning
confidence: 92%
“…Клиническая эффективность и безопасность разаги-лина (азилект) были тщательно изучены в серии крупных многоцентровых рандомизированных контролируемых исследованиях (TEMPO, PRESTO, LARGO, ADAGIO), которые продемонстрировали способность препарата уменьшать выраженность основных симптомов паркин-сонизма у больных БП с разными стадиями заболевания [11][12][13][14].…”
Section: Abstract: Parkinson's Disease Treatment Mao-b Inhibitor Runclassified
“…При применении разагили-на не отмечено также повышенной частоты таких нежела-тельных явлений АДР, как дневная сонливость, тошнота, отеки ног, импульсивно-компульсивный синдром [14].…”
Section: применение разагилина на развернутой и поздней стадиях бпunclassified
“…This has revealed that 35% of MAO-B activity was inhibited within one hour of administration of 1 mg rasagiline in healthy volunteers. 18,19 (11) C-I-deprenyl PET was able to detect decrease MAO-B activity in the thalamus and basal ganglia immediately after a 10-day period of administering rasagiline to healthy volunteers. Activity returned to normal over six weeks, consistent with the half-life for de novo enzyme synthesis.…”
Section: Dovepressmentioning
confidence: 99%